Branding Image Strategy in Enhancing the Competitive Advantage of Pondok Pesantren Islamic Center Bin Baz Yogyakarta - Rif'an Wachid Sumardi; Fitri Nur Mahmudah; Ngatmin Abbas; Muh. Fatahillah Suparman (Al Hikmah: Journal of Education, 2023)
A brand image is a collection of consumer assumptions about a brand that are formed from various sources. A positive organizational image is a valuable asset because it influences stakeholder perceptions of organizational communications and activities in a variety of ways. The brand image of an educational institution is an important step in achieving the institution's maximum public reputation. An educational institution's overall image is made up of all of its components. The goal of this research was to discover the methods or steps taken by the Islamic Center bin Baz Islamic boarding school in Yogyakarta in developing a branding image in order to increase competitiveness and avoid falling behind other educational institutions. The approach used in this study is qualitative. According to the study's findings, the Bin Baz Islamic Center Islamic Boarding School's Brand Building Strategy involves the following stages: Analyzing the reasons for choosing a brand, Developing branding programs, developing branding activities in accordance with the program, forming a branding team, determining the media used for branding, increasing the role of public relations in branding, and analyzing parents' satisfaction with the results.